2016
DOI: 10.9790/3008-1105036063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida Co-Infections among Patients with Pulmonary Tuberculosis in Emuoha, Rivers State, Nigeria.

Abstract: Candida spp have been one of the co-infection challenges facing the patients suffering frompulmonary tuberculosis 300 clinical specimen of sputa and oral swabs were collected from hospitalized tuberculosis patients for isolation of Candida spp. The patients were divided into two (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…It may be assumed that some of the devastating effects of TB on infected persons might result from the synergistic actions of both organisms. A similar study [9] had a prevalence of 25.3% TB Candida co-infection and Candida albicans were the most prevalent species as also observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It may be assumed that some of the devastating effects of TB on infected persons might result from the synergistic actions of both organisms. A similar study [9] had a prevalence of 25.3% TB Candida co-infection and Candida albicans were the most prevalent species as also observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…were equal in both males and females, [14] in their study found Candida infection to be more in males than in females. Similarly, [9] observed that Candida infections were significantly high in males (26.1%) than in females (23.1%). In this study, the prevalence of TB Candida co-infection was high among females (19.4%) compared to males (15.1%) and this agrees with the study conducted by [3] who observed that TB Candida co-infections were significantly high among female patients (62.5%) compared to male patients (29.4%).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations